The management of oral candidosis in diabetic patient with maxillary Herpes Zoster - Kus Harijanti; Dwi Setyaningtyas; Isidora KS (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Oral candidosis is an infection caused by mainly Candida albicans. Candida species are common normal flora in the oral cavity and have been reported to be present in 40% to 60% of the population. Candida is predominantly an opportunistic infectious agent. Infection frequency has increased because of the presence of both local and systemic risk factors. The elderly age and diabetes mellitus may decrease the amount of saliva (xerostomia) and potentially increase the risk of colonization and secondary infection by Candida. Herpes Zoster (HZ) is a manifestation of the reactivation of latent varicella zoster virus. It is characterized by unilateral, painful, vesicular rash with a dermatomal distribution. The clinical manifestations of this disease can erupt to the skin and mucous membrane. If maxillary nerve is involved, the lesion can appear on unilateral facial skin and oral mucous membrane. Purpose: The purpose of this paper is to report and discuss the difficulties in managing the oral candidosis in elderly patient (57 year old male) who suffered from maxillary Herpes Zoster and diabetes mellitus. Case management: At first, the patient was treated with 2% chlorhexidine gluconate and mycostatin oral suspension as topical antimycotic and reffered to dermathology clinic for viral infection treatment, however the oral candidosis did not improved. Subsequently, ketokonazole tablet was given three times daily for three weeks and regulated blood glucose level. In systemic antifungi (ketokonazole) treatment the oral candidosis disappeared. Conclusion: In this case, it is conclude that the management of oral candidosis are adequate, antiviral, blood glucose level regulating and systemic antifungal therapy.